Building a Culture of Disaster Preparedness in the Health Sector: Strengthening Community Capacity - Fasrini, Ulya Uti; Susanto, Tommy; Yunanda, Rezko (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
The natural disaster of an earthquake with the potential to cause a tsunami is still a latent danger along the coast of West Sumatra. One of the efforts in disaster management is mitigation by building a culture of disaster preparedness in the health sector, starting with intensive training. The purpose of this training was to increase the capacity of the trainees. A total of 21 out of 25 participants fully participated in the activity. This service activity was carried out in several stages, starting from the planning and preparation stage, the implementation stage, and the evaluation stage. The training method is a participatory approach with an andragogy education model. We assessed capacity improvement objectively using pre and post-test assessment sheets. Most participants were 50-60 years old and had never participated in disaster training. Analysis using paired samples t-test showed a significant increase in participants' knowledge capacity (p<0.05), from an average of 69.4 to 91.2. An evaluation of partner satisfaction at the end of the activity completed the activities. Participants were satisfied with the material the resource persons presented and the tasks. The participants considered the duration of training sufficient. Participants expect to participate in further training for specific subjects.